Evaluation of tritium retention in plasma facing components during JET tritium operations. (15th December 2021) - Widdowson, Anna; Coad, J Paul; Zayachuk, Yevhen; Jepu, Ionut; Alves, Eduardo; Catarino, Norberto; Corregidor, Victoria; Mayer, Matej; Krat, Stepan; Likonen, Jari; Mizohata, Kenichiro; Rowley, Chris; et al.
Abstract: An assessment of the tritium (T) inventory in plasma facing components (PFC) during JET T and deuterium-tritium (DT) operations is presented based on the most comprehensive ex situ fuel retention data set on JET PFCs from the 2015-2016 ILW3 operating period is presented. The global fuel retention is 4.19 × 10 23 D atoms, 0.19% of injected fuel. The inner divertor remains the region of highest fuel retention (46.5%). The T inventory in PFCs at the end of JET operations is calculated as 7.48 × 10 22 atoms and is informative for accountancy, clean-up efficacy and waste liability assessments. The T accumulation rate at the upper inner divertor during JET DT operations has been used to assess the requirements and frequency of operation of a new laser induced desorption diagnostic to be installed on JET for the final DT experiments in 2023.